2013
DOI: 10.1002/adma.201304867
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogenated Uniform Pt Clusters Supported on Porous CaMnO3 as a Bifunctional Electrocatalyst for Enhanced Oxygen Reduction and Evolution

Abstract: Hydrogenated uniform Pt clusters supported on porous CaMnO3 nanocomposites are synthesized and investigated as a new electrocatalytic material for oxygen reduction and evolution reactions. Due to the synergistic effect of Pt and CaMnO3, the nanocomposites exhibit superior activity and durability to the benchmark Pt/C catalyst.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
148
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 246 publications
(155 citation statements)
references
References 44 publications
6
148
1
Order By: Relevance
“…Also, Chen et al reported the loading of Pt clusters on porous CaMnO 3 nanoparticles with carbon as support as a bifunctional ORR/OER catalyst with excellent activity and durability. [108] …”
Section: Metal/metal Oxide/carbon Compositesmentioning
confidence: 99%
“…Also, Chen et al reported the loading of Pt clusters on porous CaMnO 3 nanoparticles with carbon as support as a bifunctional ORR/OER catalyst with excellent activity and durability. [108] …”
Section: Metal/metal Oxide/carbon Compositesmentioning
confidence: 99%
“…20 Because of its low cost, nontoxic, chemical and thermal stability, oxidation resistance in the air, it has been comprehensively studied as thermo-electric material, rechargeable batteries materials, oxygen electrocatalysis, catalyst carriers, and so on. [21][22][23][24] In this paper, we discussed the possibility of CMO to serve as the buffer layer in hybrid halide perovskites solar cells.…”
Section: Introductionmentioning
confidence: 99%
“…[ 8,10,12 ] In the case of transition metal oxides, including perovskites, while they have demonstrated precious metal-like OER activity in base, their low electrical conductivity results in unsatisfactory ORR activity. [ 15,[27][28][29][30][31] Na-air batteries are currently of immense interest because of their high capacity and energy density, as well as the abundance of Na compared to Li. While nonaqueous Na-air batteries have been predominantly investigated, [32][33][34] they suffer from the formation of solid discharge products such as Na 2 O 2 and NaO 2 on the surface of the air electrode, which are Effi cient and cost-effective bifunctional electrocatalysts for oxygen evolution reaction (OER) and oxygen reduction reaction (ORR) are of vital importance in energy conversion and storage devices.…”
Section: Introductionmentioning
confidence: 99%